Finite Difference Method Simulation on Effect of Blood Perfusion on Temperature Distribution of Female Human Skin - Wahyudi, Slamet (International Journal of Mechanical Engineering Technologies and Applications, 2022)
Bioheat transfer is a combination of heat transfer and biology process comprising of transfer of heat from human living tissue to the environment. This study aims to estimate the temperature distribution of female humanâ€™s skin. In this study, effect of varied blood perfusions of 1.5, 2.0, 2.5 and 3.0 kg/s.m3 on bioheat transfer of female human skin, which was modeled into four layers, was simulated. To address this issue, one-dimensional unsteady state finite difference method was applied in this study. Â Result of this study informed that the finite difference method can be used to solve the bioheat transfer equation and to estimate temperature distribution of different skin layers of female human. In this study, blood perfusion affects temperature distribution in the four layers of unstable women's skin. The highest blood perfusion of 3 kg/s.m3 resulted in more homogeny temperature distribution of different skin layers. This circumstance occurred since higher blood perfusion increases heat transfer between blood and skin layers.